Synthesis and characterization of MSU-2 synthesized by using tetraethylorthosilicate and Triton X-100 - Lee, X.Y. (Institute of Physics Publishing, 2020)
Adsorption technology is one of the well-established gas separation techniques as it can minimize cost and energy requirement for CO2 separation. Mesoporous silicas such as MSU-2 appears to be a good adsorbent as it comprises of three-dimensional (3D) wormhole framework structures that are highly interconnected which minimize the diffusion resistance of CO2 through its pore structure. Current study focus on the preparation of MSU-2 and investigation on the CO2 adsorption on the synthesized MSU-2. In this study, MSU-2 was prepared by using tetraethylorthosilica (TEOS) as a source of silica in the presence of non- ionic polyethyleneoxide (PEO)-based surfactants under an acidic condition where the pH is 2 at 55 Â°C for 48 hours via the fluoride-assisted two-step synthesis process. The two main steps involved are hydrolysis of TEOS and condensation of silica. The morphology, crystallinity, functional groups and pore characteristics of MSU-2 were investigated by using characterization method of Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-Ray (EDX) Spectrometry, X-ray Diffractometer (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Brunauer-Emmett-Teller (BET). The synthesized MSU-2 was well crystallized and possessed a uniform monodisperse microspherical morphology with BET surface area, pore volume and pore size of 964 m2/g, 0.98 cm3/g and 4.1 nm, respectively. All the characterization results showed that MSU-2 was successfully synthesized via solution precipitation method. In conclusion, the high BET surface area of the synthesized MSU-2 shows that MSU-2 is a very potential candidate as a good adsorbent for gases. Â© Published under licence by IOP Publishing Ltd.